Impact of Meteorological Conditions on the Photocatalytic Efficiency and Stability of Titanium Dioxide-Based Paint - Muhammad, Sunusi Dayyab; Usman, Muhammad Mudassir; Muhammad, Abdullahi; Aliyu, Maimuna; Abubakar, Abubakar (Balai Publikasi Indonesia, 2025)
Photocatalytic paints have proven to be a promising solution for combating air pollution in urban environments by breaking down harmful pollutants into harmless by-products. These paints interact with meteorological parameters when exposed outdoors, and we have investigated the influence of these parameters on the degradation of the exposed paint. We conducted experiments in a controlled laboratory in which samples of the photocatalytic paint were exposed to different temperatures and humidity levels. Using a standardized test method, we determined the constant reaction rate and analyzed the data to understand the effects of temperature and humidity on photocatalytic efficiency. The results show a significant effect of temperature and humidity on the constant reaction rate. Temperatures from 10°C to 30°C and humidities from 10% to 50% were found to increase the reaction rate, leading to an improvement in photocatalytic efficiency. However, too wide a temperature range (30℃ to 60℃) and too high a humidity (55% to 80%) had a negative effect on the thermal stability of the paint and its long-term durability. Over time, we observed an increasing loss of adhesion and fading of the paint as temperatures and humidity increased, leading to a deterioration of the photocatalytic paint. In summary, while moderate temperatures and humidity improve photocatalytic efficiency, extreme conditions can negatively affect the stability and long-term performance of the paint.